2022
DOI: 10.1177/17562864221138144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-invasive brain stimulation in dystonia: a systematic review and meta-analysis

Abstract: Background: Deep brain stimulation is a highly effective treatment of dystonia but is invasive and associated with risks, such as intraoperative bleeding and infections. Previous research has used non-invasive brain stimulation (NIBS) in an attempt to alleviate symptoms of dystonia. The results of these studies, however, have been variable, leaving efficacy unclear. Objectives: This study aimed to evaluate the effects of NIBS on symptoms of dystonia and determine whether methodological characteristics are asso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 128 publications
0
4
0
Order By: Relevance
“…However, the CD network included a hub in the cerebral cortex [16], and authors suggested a that this site could form a therapeutic target for NIBS. Given the relatively poor success rate of previous noninvasive brain stimulation targets in dystonia [11,34], we sought to test the neurobiological effects of modulation of this site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the CD network included a hub in the cerebral cortex [16], and authors suggested a that this site could form a therapeutic target for NIBS. Given the relatively poor success rate of previous noninvasive brain stimulation targets in dystonia [11,34], we sought to test the neurobiological effects of modulation of this site.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple different rTMS targets have previously been probed to treat dystonia, including M1, S1, ACC, dorsal premotor cortex, and cerebellum [11], yet there is no consensus as to the optimal target(s), and the overall efficacy of rTMS in dystonia has remained weak [11,34]. Only two studies have previously targeted S1, both applying conventional low-frequency rTMS, in specific types of dystonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations